Clinical Characteristics and Prognostic Factors of Lung Cancer in Korea: A Pilot Study of Data from the Korean Nationwide Lung Cancer Registry - Kim, Ho Cheol (Tuberc Respir Dis (Seoul), 2019)
BACKGROUND: Lung cancer is a leading cause of morbidity and mortality worldwide, and the incidence continues to rise. Although many prognostic factors have been identified, the clinical characteristics and outcomes in Korean lung cancer patients are not well defined. METHODS: Of the 23,254 new lung cancer cases registered at the Korea Central Cancer Registry in 2013, total 489 patients from 19 hospitals were abstracted by the Korean Central Cancer Registry. The clinical data retrospectively analyzed, patients were followed up until December 2015. RESULTS: The median age was 69 years (interquartile range, 60–74 years); 65.4% were male and 62.1% were ever-smokers. Cough was the most common initial symptom (33.5%); 13.1% of patients were asymptomatic. While squamous cell carcinoma was the most common subtype in male patients (37.2%), adenocarcinoma was the most frequent histological type in all patients (48.7%) and females (76.3%). The majority of patients received treatment (76.5%), which included surgery, radiation therapy, and chemotherapy. Older age (hazard ratio [HR], 1.037), lower body mass index (HR, 0.904), ever-smoker (HR, 2.003), small cell lung cancer (HR, 1.627), and distant metastasis (HR, 3.990) were independent predictors of mortality. Patients without symptoms (HR, 0.387) and without treatment (HR, 0.364) were associated with a favorable outcome in multivariate Cox analysis. CONCLUSION: Lung cancer in Korea occurs predominantly in elderly patients, with adenocarcinoma being the most frequent subtype. The prognosis was poorer in ever-smokers and older, malnourished, and untreated patients with advanced lung cancer.